Objective and subjective measures of dalfampridine efficacy in clinical practice. Issue 3 (July 2018) - Klineova, Sylvia; Farber, Rebecca; Friedman, Joshua; Farrell, Colleen; Lublin, Fred D; Krieger, Stephen
Background: Multiple sclerosis affects mobility in over 80% of patients. Dalfampridine is the only approved treatment for walking impairment in multiple sclerosis. We assessed dalfampridine utilization in our practice and investigated response using timed 25 foot walk (T25FW) improvement and a patient-reported ambulation inventory. Methods: Chart review identified patients with multiple sclerosis for whom dalfampridine was prescribed. T25FW data were extracted from medical records. Participants completed a dalfampridine-specific version of the multiple sclerosis walking scale (dMSWS-12) to assess the qualitative impact of dalfampridine on ambulation. We evaluated two responder categories: liberally defined as any improvement in T25FW; and over 20% T25FW improvement. Results: The dMSWS-12 questionnaire was completed by 39 patients. Eighteen patients (46%) did not show any T25FW improvement. Of the 21 patients (54%) with T25FW improvement, four patients (11%) showed improvement greater than 20%. Analysis of dMSWS-12 scores showed a median score of 40 (range 12–60). Eleven patients (28%) showed no improvement (dMSWS-12 score ≤36). In contrast to objective T25FW improvement (54%), 28 patients (72%) reported improvement in walking ability (dMSWS-12 score ≥37). Conclusion: Our results suggest that T25FW alone might not be sufficient for response characterization and that adding patient-reported measures may further elucidate the therapeutic response.